SLC1A5 Prefers to Play as an Accomplice Rather Than an Opponent in Pancreatic Adenocarcinoma - Xu, Fangshi; Wang, Hai; Pei, Honghong; Zhang, Zhengliang; Liu, Liangliang; Tang, Long; Wang, Shuang; Ren, Bin-Cheng (Frontiers in Cell and Developmental Biology, 2022)
Background Ferroptosis regulator gene, SLC1A5 acts a dual role in cancer regulation. However, the roles of SLC1A5 in pancreatic adenocarcinoma (PAAD) remains elusive. Methods SLC1A5’s expression and somatic mutation information were determined by TCGA, GEO, Oncomine and cBioPortal databases. Its prognostic value was assessed in TCGA cohort and was validated in three independent cohorts. The effects of SLC1A5 on tumor immune microenvironment were analyzed by CIBERSORT algorithm, ssGSEA method, TISIDB and TIMER databases. ‘oncopredict’ R package, TIDE algorithm, ImmuneCellAI online tool, GSE35141 and GSE59357 datasets were used to ascertain its therapeutic correlations. GSEA and Western blot were applied to reveal the effects of SLC1A5 on mTORC1 signaling pathway and ferroptosis process. The biofunctions of SLC1A5 were assessed by MTT, wound-healing, transwell, and xenograft assays. Results SLC1A5 was significantly upregulated in PAAD samples, but not commonly accompanied with somatic mutation (2.3%). Overexpression of SLC1A5 led a poor prognosis, and was identified as an independent prognostic factor. Moreover, high SLC1A5 expression suppressed antitumor immune process by changing the infiltrating levels of immune cells. As for therapeutic correlations, SLC1A5 was related to the efficacy of Dasatinib, Sunitinib, Sorafenib and Imatinib, but may not predict that of radiotherapy, chemotherapeutic drugs, and immune checkpoints inhibitors (ICIs). Notably, overexpression of SLC1A5 could activate mTORC1 signaling pathway and may increase the cellular sensitivity to ferroptosis. Finally, overexpression of SLC1A5 markedly promoted the proliferation, migration, and invasion of pancreatic cancer cells. At the in vivo level, SLC1A5 deletion inhibited tumor growth in a mice xenograft model. Conclusions SLC1A5 prefers to play as an accomplice rather than an opponent in PAAD. Our findings provide novel insights into PAAD treatment.